Numerical simulation of dynamic characteristics of rectangular single leg thin-wall hollow piers with different pier heights - Xinru Shen; Zhenghua Zhou (地震科学进展, 2021)
Firstly，this paper introduces the purpose and significance of studying the characteristics of high and low piers，and summarizes the research status of dynamic and static characteristics of high and low piers at home and abroad. Then，five kinds of pier models with different heights are established with the aid of the finite element software ABAQUS. Modal analysis is carried out，the natural frequency and mode shape are extracted，the characteristics of natural vibration are analyzed，and three different groups of ground motions are input along the two directions respectively. The displacement and acceleration response of the structure are compared and analyzed. The results show that：for the same mode，with the decrease of pier height，the natural frequency will increase and the change of pier height affects the higher mode. The decrease of pier height can significantly reduce the displacement and acceleration response of the structure. The difference of displacement and acceleration response of the structure caused by different seismic input is significant.